(untitled) (Journal of Health Informatics in Africa, 2013)
Background and Purpose: A number of African countries have in recent years deployed online, web-based health information systems (HIS). We look at the opportunities and challenges of this new architecture by comparing recent HIS implementations in Ghana and Kenya. Methods: This article is based on several years of involvement by the authors in a large action research project (the Health Information Systems Programme) that focuses on developing and implementing health information systems. The project has a strong focus on active participation of the researchers in the research context, drawing on the Scandinavian tradition of participatory action research. All authors have been directly involved in the HIS implementations in Ghana and/or Kenya discussed in this article. Results: We show how the two countries studied in this article, Ghana and Kenya, have rapidly transitioned from having an offline, decentralised HIS based on standalone software installations, to a new architecture that is online, web-based and centralised. Conclusions: The cases of Ghana and Kenya demonstrate how a web-based, online architecture for HIS provides a number of advantages over the standalone, offline systems that have been the norm until recently. However, important aspects of such implementations, like developing skills and policies for system administration and ensuring system ownership need emphasis in order to ensure the long-term sustainability of these systems.